Jeremiah 26-52 - Sharp, Carolyn (W. Kohlhammer GmbH, 2021)
This commentary illumines Jer 26-52 through historical, literary, feminist, and postcolonial analysis. Ideologies of subjugation and resistance are entangled in the Jeremiah traditions. The reader is guided through narratives of extreme violence, portrayals of iconic allies and adversaries, and complex gestures of scribal resilience. Judah's cultural trauma is refracted through prose that mimics Neo-Babylonian colonizing ideology, dramatic scenes of survival, and poetry alight with the desire for vengeance against enemies. The commentary's historical and literary arguments are enriched by insights from archaeology, feminist translation theory, and queer studies. This commentary illumines Jer 26-52 through historical, literary, feminist, and postcolonial analysis. Ideologies of subjugation and resistance are entangled in the Jeremiah traditions. The reader is guided through narratives of extreme violence, portrayals of iconic allies and adversaries, and complex gestures of scribal resilience. Judah's cultural trauma is refracted through prose that mimics Neo-Babylonian colonizing ideology, dramatic scenes of survival, and poetry alight with the desire for vengeance against enemies. The commentary's historical and literary arguments are enriched by insights from archaeology, feminist translation theory, and queer studies
Keywords: Altes Testament; Kommentar; Old Testament; Tanach; Tora